2015
DOI: 10.1111/1750-3841.13006
|View full text |Cite
|
Sign up to set email alerts
|

Authentication of Whey Protein Powders by Portable Mid‐Infrared Spectrometers Combined with Pattern Recognition Analysis

Abstract: A rapid, simple and accurate method was developed to authenticate commercial whey protein products by using portable mid-infrared spectrometers combined with chemometrics, which could help ensure the functionality of whey protein ingredients in food applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…This could be attributed to better coupling of the optical element within the optical train for the dedicated ATR (portable 4500 series) instrument as compared to the ATR module within the laboratory spectrometer [40]. Further, the larger number of PLS-factors suggests that the laboratory ATR-IR assay may be less robust than the portable ATR-IR counterpart, by virtue of its reliance upon additional factors that are relatively noisy [41]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to better coupling of the optical element within the optical train for the dedicated ATR (portable 4500 series) instrument as compared to the ATR module within the laboratory spectrometer [40]. Further, the larger number of PLS-factors suggests that the laboratory ATR-IR assay may be less robust than the portable ATR-IR counterpart, by virtue of its reliance upon additional factors that are relatively noisy [41]. …”
Section: Discussionmentioning
confidence: 99%
“…The portable ATR-IR assay showed higher utility (higher RPD and RER values), and more flexibility for field application [40, 41] than the laboratory grade ATR-IR assays reported in the present study, and that previously reported for bovine serum IgG [24]. Correlation between the RID-based IgG analyses and ATR-IR based assays was better than that previously reported for transmission-IR based IgG assays for alpaca [26] and equine [25] sera, but worse than that achieved for transmission and ATR-IR based bovine IgG assays [24].…”
Section: Discussionmentioning
confidence: 99%
“…The strongest peaks and main absorptions regions are within the wavenumber range of 1800 to 900 cm -1 . In the WPC characterization, the main concern is with absorption as result of vibrations in the amide bonds of amino acids and proteins, primarily Amide I (C=O Pure WPC 1 stretching vibration -peak 4, centered at approximately 1632 cm −1 ), Amide II (N-H bending and C-N stretching vibrations -peak 5 at approximately 1531 cm −1 ) and also Amide III (mainly C-N, stretching vibration -peak 8, around 1250 cm -1 ) [8,25]. Peak 3 is associated to vibrational groups of C=O groups of lipids.…”
Section: Wpc Characterizationmentioning
confidence: 99%
“…Peak 3 is associated to vibrational groups of C=O groups of lipids. The band at 1450 cm −1 (peak 6), corresponds to the bending of C-H bonds in CH2 groups, while peak 7 (1392 cm −1 ) to the stretching of C=O in carboxylic acid groups [8]. Finally, the vibration in the 1130 to 1000 cm −1 range (region 9) is linked to stretching vibrations of C-OH, C-C and C-O-C present in in carbohydrates, mainly lactose [25,26].…”
Section: Wpc Characterizationmentioning
confidence: 99%
See 1 more Smart Citation